Trg lesnih peletov v Sloveniji in širše - Krajnc, Nike (Gozdarski vestnik, 2016)
The use of pellets in Slovenia and European Union is growing in the recent years and will, according to projections, continue to grow. The momentary conditions on the market are very uncertain (above all due to mild winters, falling prices of fossil fuels, and increase of capacities), what has been experienced also by the largest pellets producers in Europe. In the past we had reported about low quality level of pellets on the Slovenian market, therefore the Forestry Institute of Slovenia offered its support for establishing and ensuring appropriate quality of all links of the production chain of wood energy sources in 2015. Introducing the scheme and acquiring the S4O label, smaller producers prove on the market that they achieve and maintain a certain quality level. The S4Q scheme and trademark have been successfully introduced with five Slovenian pellets producers.
Keywords: lesna goriva; lesna biomasa; kakovost; trg; Slovenia; Slovenija; lesni paleti